Epilepsy with eyelid myoclonias (Jeavons syndrome): An electro-clinical study of 40 patients from childhood to adulthood. (April 2021) - Nilo, Annacarmen; Crespel, Arielle; Genton, Pierre; Macorig, Greta; Gigli, Gian Luigi; Gelisse, Philippe
Highlights: Jeavons syndrome is a reflex epilepsy with onset in childhood (6.2 ± 3.4 years). There is a female preponderance (sex ratio F/M = 3.44). Intellectual disability and/or psychiatric disorders are not rare. Focal EEG abnormalities are frequently observed, in two-third of the cases. Photoparoxysmal response appears different from other photosensitive syndromes. Abstract: Purpose: To describe the typical and atypical clinical and electroencephalographic (EEG) features of 40 patients with Jeavons syndrome (JS). Method: Retrospective analysis from two French tertiary centers. Results: Forty patients were enrolled (31 females and 9 males; sex ratio F/M = 3.44; mean age at epilepsy onset: 6.2 ± 3.4 years [range: 1–15 years]). A positive family history of generalized genetic epilepsy was reported by 13 patients (32.5 %). Eyelid myoclonias with or without absence were the seizure onset in 29 patients (72.5 %), and generalized tonic-clonic seizures in 11 (27.5 %). Over the course of the disease, all had absences. Intellectual disability and psychiatric disorders were reported in 14 (35 %) and 18 patients (45 %), respectively. Focal EEG abnormalities were observed in 65 % of patients, with a posterior (57.7 %) or anterior (30 %) distribution. Generalized EEG discharges were identified in 37 patients (92.5 %). Epileptiform abnormalities were activated during NREM sleep and increased upon awakening. Response to intermittent light stimulation (ILS) was observed in 34 patients (85 %), with an unusual pattern of epileptiform abnormalities at the same frequency of the flashes in 20 patients. Patients with all seizure types were more likely to have this response (p = 0.017). Conclusion: JS is a lifelong genetic epileptic syndrome with onset in childhood, female preponderance, and a positive family history of epilepsy in one-third of the cases. Focal EEG abnormalities are frequent. Response to ILS appears different from other photosensitive syndromes, with an unusual pattern of photo-induced abnormal synchronization. Intellectual disability and psychiatric disorders are not rare.